The Analysis of the Character of Love for the Motherland Through National Songs in Students with Mentally Impaired - Rizka Venza Taufan Utama Rizka Venza Taufan Utama; Tri Linggo Wati Tri Linggo Wati (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Love for the homeland is loving the country and always taking part in maintaining culture, economy, language and politics for the sake of the integrity and sovereignty of the nation. However, mentally retarded children have not yet instilled the character of love for the country properly. This research aims to analyze the character of love for one's country through national songs in students with intellectual disabilities. This research uses a qualitative method through a case study approach with the subjects involved in the research being 1 mildly mentally retarded student and 1 moderately mentally retarded student in class III. Data collection techniques through observation, interviews and documentation. The data validation technique uses triangulation techniques. The results of this research state that D is able to recognize national song titles independently and is able to understand national song composers using the help of the media and D is able to sing national song lyrics. Meanwhile, N cannot yet know the title, creator and singing of the national song. The inability of mentally retarded students to gain knowledge of national songs is influenced by intellectual limitations or IQ.